FORMING A COMPETITIVE ADVANTAGE TQM STRATEGY FOR IMPROVING THE QUALITY OF EDUCATIONAL INSTITUTIONS - Maimuna, Ida; Mundiri, Akmal; Muali, Chusnul; Munif, Muhammad; Khaer, Abu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore the implementation of TQM as the main strategy for improving the quality of educational institutions. By understanding the essence of TQM and its impact on educational institutions, it is hoped that we can make a significant contribution to facing various challenges and competition in the education sector. In this way, we can form educational institutions that are not only of high quality but also capable of producing graduates who are ready to compete on the global stage. This research uses a qualitative case study-type method by conducting research that aims to describe the problem and carry out an analysis of the problems that occur. Researchers collected data through several stages, such as observation and direct observation at the research site. Interview, interviewing a number of informants at the research site. Observation: visiting the research site. Documentation study, analysing documents related to research. The research was carried out at the MI Tarbiyatul Islam institution in Kandangjati Kulon, Kraksaan, Probolinggo. Based on the results of the research conducted, it shows that several innovations adopted by MI Tarbiyatul Islam include: (1) Integrated Learning Technology. This institution combines modern technology with the learning process, including the use of educational software, interactive learning applications, and online platforms. This not only increases student engagement but also facilitates real-time measurement and analysis of learning data. (2) Training and Development of Human Resources (HR), Realising that institutional excellence depends on the quality of human resources, MI Tarbiyatul Islam regularly provides training and development to teachers and administrative staff.